Incident microalbuminuria and complement factor mannan‐binding lectin‐associated protein 19 in people with newly diagnosed type 1 diabetes. Issue 5 (11th April 2017) - Østergaard, J.A.; Thiel, S.; Hoffmann‐Petersen, I.T.; Hovind, P.; Parving, H.‐H.; Tarnow, L.; Rossing, P.; Hansen, T.K.
Abstract: Background: Evidence links the lectin pathway of complement activation to diabetic kidney disease. Upon carbohydrate‐recognition by pattern‐recognition molecules, eg, mannan‐binding lectin (MBL), the MBL‐associated serine protease (MASP‐2) is activated and initiates the complement cascade. The MASP2 gene encodes MASP‐2 and the alternative splice product MBL‐associated protein 19 (MAp19). Both MAp19 and MASP‐2 circulate in complex with MBL. We tested the hypothesis that MAp19 and MASP‐2 concentrations predict the risk of incident microalbuminuria. Methods: Baseline MAp19 and MASP‐2 were measured in 270 persons with newly diagnosed type 1 diabetes tracked for incidence of persistent microalbuminuria in a prospective observational 18‐year‐follow‐up study. Results: Seventy‐five participants (28%) developed microalbuminuria during follow‐up. MBL‐associated protein 19 concentrations were higher in participants that later progressed to microalbuminuria as compared with those with persistent normoalbuminuria (268 ng/mL [95% CI, 243‐293] vs 236 ng/mL [95% CI, 223‐250], P = .02). Participants with MAp19 concentration within the highest quartile of the cohort had an increased risk of microalbuminuria as compared with participants with MAp19 concentration within the combined lower 3 quartiles in unadjusted Cox analysis, hazard ratio 1.86 ([95% CI, 1.17‐2.96], P = .009). This remained significant in adjusted models, eg, adjusting for age, sex, HbA1c, systolic blood pressure, urinary albumin excretion, smoking, serum creatinine, and serum cholesterol. MBL‐associated serine protease concentration was not associated with incidence of microalbuminuria. Conclusions: In conclusion, the results show an association between baseline MAp19 concentration and the incidence of microalbuminuria in an 18‐year‐follow‐up study on persons with newly diagnosed type 1 diabetes.